Chemical inhibition of Src family kinases affects major LPS-activated pathways in primary human macrophages. - Smolinska, M; Horwood, N; Page, T; Smallie, T; Foxwell, B (2008)
Understanding the signalling mechanisms controlling inflammatory cytokine production is pivotal to the research of both acute and chronic immune disorders. Tyrosine phosphorylation is one of the earliest events to occur in response to an immune challenge yet the role of specific tyrosine kinases in inflammatory cytokine production has been difficult to ascribe due to conflicting literature. Here we show that the pyrazolo pyrimidine compound PP2, a selective inhibitor of Src family kinases (SFK), can inhibit LPS-induced TNF production as well as a number of other inflammatory cytokines. In addition, we show similar effects of PP2 on cytokine production when induced by other TLRs, (1, 2 and 5-8), indicating that SFK are important common regulators of TLR signalling. PP2 suppressed the activity of both TNF and IL-10 driven reporter genes, suggesting that this activity is mediated at the level of transcription. Interestingly, however, PP2 had no significant effect on the activation of NF-kappaB, or on p42/44 ERK, p46/54 JNK or p38 MAPK phosphorylation. In contrast, PP2 did inhibit AP-1 nuclear accumulation in response to LPS. Taken together, these findings show that the Src kinases are able to control inflammatory cytokine production at the transcriptional level independently of NF-kappaB, and highlight the role of the AP-1 family of transcription factors as downstream mediators of Src kinase action.